FMS SCORES AND INJURY RISK: A CROSS-SECTIONAL STUDY OF DOMESTIC CRICKET PLAYERS IN KARACHI (The Research of Medical Science Review, 2025)
This study aimed to assess the association between Functional Movement Screening (FMS) scores and injury incidence among domestic cricket players in Karachi. A total of 150 male players aged 18-35 years were included, each of whom underwent FMS testing and provided details on their injury history. FMS scores were used to identify movement deficiencies, with scores ≤14 indicating potential injury risk. The study employed a cross- sectional design, and data were analyzed using descriptive statistics, chi-square tests, and logistic regression analysis to explore the relationship between FMS components and injury history. Results revealed that 50% of the players reported having a history of injuries. The Low FMS Score (≤14) group showed a higher proportion of players with injury histories (53.3%) compared to the High FMS Score (>14) group (46.7%). Logistic regression analysis identified key FMS components as significant predictors of injury risk. Deep Squat, Shoulder Mobility, and Trunk Stability Push-up were found to significantly increase the likelihood of injury, with odds ratios of 1.5, 1.6, and 1.4, respectively. Conversely, components such as Inline Lunge and Rotary Stability did not show a significant relationship with injury risk. This study highlights the potential of FMS as a tool for identifying players at risk of injury in cricket. Targeted interventions to improve movement patterns in areas like Deep Squat and Shoulder Mobility could reduce injury incidence and enhance overall player performance. Future research should investigate the long-term effects of FMS-based interventions in cricket and other sports to further validate these findings.